2019
DOI: 10.1590/fst.28117
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, thermal and rheological properties of three native corn starches

Abstract: Native starch was isolated from two corn landraces (blue and white) and a hybrid variety and then characterized for its physicochemical, thermal and rheological properties. The hybrid variety showed the highest starch yield, with its starch showing the highest fat, moisture and protein content but the lowest onset temperature of gelatinization. The hybrid corn starch also showed the highest G' and G" values. The tested starches showed similar T p , T c , and ΔH values. The amylose contents ranged from 21.5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Finally, the treated produced cassava starch pastes with reduced elastic properties. This result was in accordance with the study conducted by Bustillos et al, (2018) for corn starches.…”
Section: Effect Of Sonication On Rheological Properties Of Cassava Starch Pastesupporting
confidence: 93%
“…Finally, the treated produced cassava starch pastes with reduced elastic properties. This result was in accordance with the study conducted by Bustillos et al, (2018) for corn starches.…”
Section: Effect Of Sonication On Rheological Properties Of Cassava Starch Pastesupporting
confidence: 93%
“…The gelatinization temperatures of the nonextruded corn, quinoa, and fava bean flours were 72.1, 64.5 and 68.7°C, respectively. These results were similar to those reported by Bustillos-Rodríguez et al (2018), ranging between 70.6 and 72.2°C. Moreover, Arzapalo et al (2015) reported that the gelatinization temperature of quinoa starch was 66°C, and Wani et al (2016) indicated that fava beans' starch gelatinization temperature ranged between 66.6 and 70.59°C.…”
Section: Chemical Compositions Of Extruded Formulationssupporting
confidence: 92%
“…The starch was isolated according to the methodology proposed by Sandhu et al [ 44 ] and Bustillos-Rodríguez et al [ 45 ]. Corn kernels were finely ground using a food-grade stainless steel high-speed electric mill (Semillas de Vida, Model SV-MO-100T, Cuernavaca, Morelos, Mexico).…”
Section: Methodsmentioning
confidence: 99%